The Effect of The Addition of Skim Milk Powder to Broiler Liver Nuggets on Physicochemical and Organoleptic Quality (Jurnal Ilmu dan Teknologi Hasil Ternak, 2023)
Chicken nuggets are a popular product among the public, but because of the relatively high price, not all people can consume them. The development of innovation in processed nugget products is increasingly diverse, such as using chicken liver added skim milk powder to improve nutritional quality, physical quality, and consumer preferences. The purpose of this research was to determine the effect of the addition of skim milk powder on broiler liver nuggets in terms of moisture content, water activity (Aw), and physical quality. The research method was a laboratory experiment with a completely randomized design (CRD) is P0 (0%), P1 (5%), P2 (7%), and P3 (10%) for differences adding skim milk powder and the data were analyzed using analysis of variance or ANOVA. The results showed that the addition of skim milk powder was not significantly different (P>0.05) on moisture content, water activity (Aw), texture, and physical quality of yield and color (L*, a*, b*), but had an effect on significantly (P<0.05) in organoleptic (color, taste, and odor) and some of the essential amino acids. The conclusion was that the addition of skim milk powder on 10% was used as a treatment best with moister content, water activity (Aw), and texture, than for physical quality, the best addition was 10% for yield, color, tasteMand color L* (brightness), a* (redness) b* (yellowness). As a reference for further research can compare other commodity types of the liver.